A hit fejlődése és a normativitás – keresztyén perspektívából - Tibor SITKU (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2023)
Development of Faith and Normativity – A Christian Perspective. The study deals with the question of normativity: first, in the context of James Fowler’s theory of faith development and later in the sense of the Christian concept of faith. The question we seek to answer is: can we expect in the light of Fowler’s and the Christian understanding of faith that we should grow in our faith? In order to answer this question, we will first consider the meaning of normativity and then examine the normativity of faith development in the context of both the Fowlerian and the Christian interpretations.